2013
DOI: 10.4161/auto.24817
|View full text |Cite
|
Sign up to set email alerts
|

Sh3glb1/Bif-1and mitophagy

Abstract: Evasion of apoptosis, which enables cells to survive and proliferate under metabolic stress, is one of the hallmarks of cancer. We have recently reported that SH3GLB1/Bif-1 functions as a haploinsufficient tumor suppressor to prevent the acquisition of apoptosis resistance and malignant transformation during Myc-driven lymphomagenesis. SH3GLB1 is a membrane curvature-inducing protein that interacts with BECN1 though UVRAG and regulates the post-Golgi trafficking of membrane-integrated ATG9A for autophagy. At t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Previous studies revealed that EB1 diffuses in cytoplasm and does not co-localize with mitochondria under basal conditions while aggregates into foci and translocates to mitochondria during mitophagy 8 9 . Based on the high homology of EB1 and EB2 ( Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies revealed that EB1 diffuses in cytoplasm and does not co-localize with mitochondria under basal conditions while aggregates into foci and translocates to mitochondria during mitophagy 8 9 . Based on the high homology of EB1 and EB2 ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The membranes of autophagosomes are derived from various membrane sources, and subsequent processes involving autophagosomes have been shown to be associated with the Beclin-1-PI3KC3 complex 6 . The protein Endophilin B1 (EB1) has been reported to interact with Beclin-1 regulating autophagosome biogenesis 7 and associate with mitochondrial membrane promoting mitochondrial degradation 8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SH3GLB1 is a member of the membrane curvaturedriving endophilin family, which regulates the post-Golgi trafficking of membrane-integrated ATG9A for autophagy. 149,150 In humans, the SH3GLB1 gene is located on chromosome 1p22, a region frequently deleted in neoplasms 151 and its expression is downregulated in a wide variety of cancers. [152][153][154][155][156] Furthermore, inhibition of endogenous expression of SH3GLB1 by RNA interference enhances the tumorigenecity of HeLa cells and SH3GLB1-knockout mice are susceptible to the development of spontaneous tumors, indicating that SH3GLB1 is indeed a novel bona fide tumor suppressor.…”
Section: Becn1 Complexmentioning
confidence: 99%
“…Indeed, BECLIN-1 , BIF-1 and UVRAG , three essential autophagy genes have been classified as tumor suppressor genes and are frequently inactivated in cancer cells leading to the promotion of cell proliferation and aggressiveness. [ 8 , 9 , 10 ] Defects and mutations in autophagy genes have also been frequently observed in neurodegenerative disorders such as Alzheimer’s disease, or familial Parkinson’s disease. [ 11 ] Since then, the development of techniques to efficiently monitor autophagy levels in cell and tissue models became a challenge to better characterize autophagy protein expression, function and deregulation in these pathologies.…”
Section: Introductionmentioning
confidence: 99%